Exploring local community perspectives on the development of river tourism along the Petagas-Putatan river in Sabah, Malaysia - Jennifer Kim Lian Chan; Tay Kai Xin; Ing Grace Phang (Elsevier Ltd, 2024)
The research delves into the perceptions regarding the necessary assistance and support required for the development of river tourism along the Petagas-Putatan River. An exploratory qualitative with a total of four focus group discussions consisting of a total of 13 local communities, two local authorities and two local representatives of the district. Assistances needed include financial, tourism trainings related to river tourism and safety, planning and itineraries, customer services, marketing, and promotion. Tourist facilities - jetties, roads, sidewalks, parking lots and retail stalls for food, drinks and souvenirs are vital support for developing river tourism. The condition of the river and local communities’ attitudes towards river cleanliness are the key issues. It contributes to the development of river tourism along river Petagas-Putatan, provide practical implications for river tourism development.